Innovative Strategies in agricultural production units: knowledge in development of new services and value chains (2023)
The world faces unavoidable challenges that force organizations to undertake actions that solve, mitigate and reverse problems arising from the lack of social, economic and environmental sustainability, with climate change being one of the most pressing. The implementation of new technologies would mean a costly transition, but fundamental and necessary to trace paths that help preserve the planet and the institutions of all kinds that exist in it. The research seeks to describe innovative strategies in agricultural production units as part of the knowledge in the development of new services and value chains. The innovation and adoption of new technologies in processes and consumption patterns will only be possible if companies manage to develop markets that provide in their value offer, the component of environmental sustainability in a transversal way in all their activities. The findings show that the adoption of innovative strategies in agricultural production companies has been slow, so the accompaniment of government entities, civil society organizations, academia, research centers and others is crucial to address these problems and generate strategies to solve them.